1983
DOI: 10.1159/000225718
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Combination Chemotherapy with <i>cis</i>-Diamminedichloroplatinum on Renal Function: Long-Term Effects

Abstract: Glomerular filtration rate (GFR) and effective renal plasma flow (ERPF) were determined in 8 patients with disseminated testicular carcinoma before, during and 1 year after termination of a combination chemotherapy with cis-diamminedichloroplatinum (CDDP). The decrease in median GFR in comparison with the pretreatment value was 15.5% at the start of the maintenance therapy, 23% at the end of the maintenance therapy and 15.5% 1 year after termination of therapy. The comparable reduction in ERPF at those instant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In spite of adequate hydration, the patients treated with cisplatin had a decrease in GFR of more than 25% from the baseline values in 29% of patients, which is similar to the value reported in the literature [10], Usually, the renal impairment is still observed at least 6 months after the end of chemotherapy and correlates with age, cumulative dose of cisplatin and the presence of dehydration [12], Hypomagnesemia is common with cisplatin doses of more than 40 mg/m2 [7] and may necessitate oral and intravenous magnesium supplements [14], In the present study, magnesium supplements were given but significant hypomagnesemia was still found in 4 patients (14%). Dur ing chemotherapy serum magnesium values decreased significantly from 1.67 ± 0.08 to 1.32 ± 0.06 mg/dl (p<…”
Section: Discussionsupporting
confidence: 87%
“…In spite of adequate hydration, the patients treated with cisplatin had a decrease in GFR of more than 25% from the baseline values in 29% of patients, which is similar to the value reported in the literature [10], Usually, the renal impairment is still observed at least 6 months after the end of chemotherapy and correlates with age, cumulative dose of cisplatin and the presence of dehydration [12], Hypomagnesemia is common with cisplatin doses of more than 40 mg/m2 [7] and may necessitate oral and intravenous magnesium supplements [14], In the present study, magnesium supplements were given but significant hypomagnesemia was still found in 4 patients (14%). Dur ing chemotherapy serum magnesium values decreased significantly from 1.67 ± 0.08 to 1.32 ± 0.06 mg/dl (p<…”
Section: Discussionsupporting
confidence: 87%
“…Our study, which included a greater diversity of tumor types, supports this initial decline in eGFR. In previous studies in which GFR and renal plasma flow were measured using exogenous filtration markers and 24-hour creatinine clearance, the observed acute and chronic declines in GFR were of larger magnitude, ranging from 12% to 23% (12,13,15,(20)(21)(22). In our study, a lower median decline in eGFR of 10 ml/min per m 2 was observed.…”
Section: Discussionmentioning
confidence: 93%
“…Its application is accompanied by doselimiting side-effects, such as nephro-, neuro-and ototoxicity (Kovacs et al, 1982;Meijer et al, 1983;Vermorken et al, 1983). Despite its long-standing and wide clinical application, the optimal schedule of CDDP, with a maximal attainable anti-tumour effect and tolerable side-effects, has never been clearly established.…”
mentioning
confidence: 99%